Covering gonality of symmetric products of curves and Cayley–Bacharach condition on Grassmannians - Francesco Bastianelli; Nicola Picoco (Forum of Mathematics, Sigma)
Given an irreducible projective variety X, the covering gonality of X is the least gonality of an irreducible curve